PENGARUH PENGETAHUAN AWAL, KEDISIPLINAN BELAJAR, DAN IKLIM KOMUNIKASI KELAS TERHADAP HASIL BELAJAR PRODUKTIF AKUNTANSI SISWA KELAS XI JURUSAN AKUNTANSI SMK NEGERI 3 BANGKALAN - Handayani, Veronika Tri (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2015)
This study aims to analyze the effect of prior knowledge, learning discipline and classroom communication climate on productive accounting learning student class XI accounting in SMK Negeri 3 Bangkalan. The population in this study is class XI student of Accounting at SMK Negeri 3 Bangkalan as many as 157 students. In this study, sampling was simple random sampling, with a total sample of 113 respondents.Techniques or methods of data collected by questionnaires and documentation. The method used is quantitative. Data analysis techniques are multiple linear regression analysis. The results showed that: There was a simultaneously significant effect of prior knowledge, learning discipline and classroom climate communication to the learning outcomes; There is a significant effect of initial partial knowledge of the learning outcomes; There was a partial significant effect of discipline to the learning outcomes; There was a partial significant effect of class communications climate to the learning outcomes